Membimbing Siswa Bermasalah Melalui Refleksi (Analisis Peran Bu Prani Sebagai Guru Bk Dalam Film “Budi Pekerti” Karya Wregas) - Putri, Nur Hikmah Okti Sania; 'Azah, Nur; Jannah, Miftahul; Nahdliyah , Hilmah Zahrotun (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The film "Budi Pekerti" by Wregas Bhanot presents an inspirational story about the role of a school counselor in guiding troubled students. This study aims to analyze the representation of the school counselor's role in the film. A qualitative research method with Teun A. van Dijk's discourse analysis approach was applied. The results of the analysis show that the character Bu Prani is represented as an ideal school counselor who is wise and compassionate in guiding troubled students. She does not punish, but always provides "reflection" which encourages students' self-introspection and positive change. This representation is relevant to the need for a new approach in education today, where punishment is considered ineffective in changing long-term student behavior. School counselors are seen as key figures in realizing this paradigm shift through dialogical and humanistic approaches. This study concludes that the figure of Bu Prani can inspire Indonesian school counselors to be more optimal and creative in guiding troubled students through reflection, not punishment. This film has the potential to become a powerful educational medium to build a new perspective in dealing with troubled students.